Пневмосистема для гідропневматичного висівного апарата - Бойко, В. Б.; Улексін, В. О.; Мілько, В. С.; Boyko, Vladyslav; Uleksin, Vasil; Milko, V. (КНТУ, 2015)
Приведені результати досліджень агрегатів пневмосистеми для ручної сівалки однозернового висіву насіння з гідропневматичним висівним апаратом, наводяться формули для інженерного розрахунку основних параметрів пневмосистеми. At the Dnepropetrovsk agricultural University proposed the method of single seed sowing of vegetable seeds. For this purpose we developed and constructed a laboratory model of the hydropneumatic sowing device, experiments which confirmed its operability. Application of the developed metering device for piece selection of seeds from seed tanks and feeding it into the zone of sowing, allows precise seeded planting seeds. To use the proposed apparatus to the mechanization of single seed sowing it is necessary to solve a number of problems, in particular to provide a hand-seeder with pneumatic system. In this paper the results of studies of aggregates of the pneumatic system for manual drill-seeded seeding with hydro-pneumatic metering system, the expressions for engineering calculation of the main parameters of the pneumatic system.
The pneumatic system for a hydropneumatic sowing device
Keywords: висівний апарат; однонасіннєвий висів; пневматична система; компресор; seed distribution vehicle; single seed; pneumatic system; compressor